Korelasi Kualitas Pelayanan Kesehatan Menggunakan Model Parasuraman, Zeithaml, dan Berry dengan Kepuasan Pasien Rawat Inap (Studi pada Rumah Sakit Hikmah Citra Medika Sengkang) - B, Khaeriah; Ruslang, Ruslang; Anggreni, Nuranisa (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2025)
The level of satisfaction of patients in hospitals, especially inpatients, is measured by the quality of health services. There are five dimensions of assessing the quality of health services according to Parasuraman, Zeithaml, and Berry according to the degree of relative importance, including, physical evidence (tangible) including physical facilities, equipment, employees and concise communication facilities (reliability), namely providing promising service capabilities that are immediate, accurate and satisfying. Responsiveness is the desire of nurses to help clients and provide services responsively. Guarantee (assurance) covers the competition, knowledge, courtesy and trustworthiness of the staff, free from danger, risk or doubt. Empathy (empathy) includes ease in establishing relationships, good communication, personal attention, and understanding of the individual needs of patients Keyword: Quality, service, patient satisfaction